2017
DOI: 10.1038/s41598-017-06609-x
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram predicted risk of peripherally inserted central catheter related thrombosis

Abstract: The use of peripherally inserted central catheters (PICCs) is increasing rapidly worldwide. A number of patient-related, clinical-related and device-related characteristics might be risk factors for PICC-related thrombosis. We retrospectively reviewed a database of 320 consecutive patients who underwent PICC insertion between December 2014 and December 2015 at the First Affiliated Hospital of Xi’an Jiaotong University to explore the potential associations between risk factors and PICC-associated thrombosis. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 32 publications
3
38
0
Order By: Relevance
“…Our study confirmed that a high D-dimer level before PICC insertion was related to symptomatic PICC-RT, especially for patients with D dimer level >0.55 mg/L. Hao et al suggested that the D-dimer level could be used as a predictor for future PICC-RT (Hao et al, 2017). A Chinese study also showed that a high D-dimer level may increase the risk of PICC-RT, especially for patients with D-dimer level >5 mg/L (Pan et al, 2014).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our study confirmed that a high D-dimer level before PICC insertion was related to symptomatic PICC-RT, especially for patients with D dimer level >0.55 mg/L. Hao et al suggested that the D-dimer level could be used as a predictor for future PICC-RT (Hao et al, 2017). A Chinese study also showed that a high D-dimer level may increase the risk of PICC-RT, especially for patients with D-dimer level >5 mg/L (Pan et al, 2014).…”
Section: Discussionsupporting
confidence: 85%
“…Hao et al . suggested that the D‐dimer level could be used as a predictor for future PICC‐RT (Hao et al., 2017). A Chinese study also showed that a high D‐dimer level may increase the risk of PICC‐RT, especially for patients with D‐dimer level >5 mg/L (Pan et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Several CRT prediction models have been reported but not externally validated (25,26), and they did not give special attention to the cancer status/type. A number of prediction models for cancer-associated venous thromboembolism have been proposed in recent years (16,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…There are risk scores for PICC-associated UEVTE, such as the Michigan Risk Score or nomograms derived from retrospective cohorts 34 ; however, these have not been optimized for patients with cancer. 35 The Khorana score on the other hand is used to predict VTE in malignancies 36 ; however, its use in predicting PICC-associated UEVTE in cancer patients is unknown.…”
Section: Assessing Risk For Secondary Upper Extremity Deep Vein Thrombosismentioning
confidence: 99%